2021
DOI: 10.1021/acsaem.1c01947
|View full text |Cite
|
Sign up to set email alerts
|

Hollow CoSx Nanoparticles Grown on FeCo-LDH Microtubes for Enhanced Electrocatalytic Performances for the Oxygen Evolution Reaction

Abstract: Hollow CoS x nanoparticles grown on FeCo-LDH microtubes (FeCo-LDH@CoS x ) were successfully developed as a highly efficient and lowcost electrocatalyst for the oxygen evolution reaction (OER) in an alkaline solution. The as-prepared FeCo-LDH@CoS x microtubes were characterized by X-ray powder diffraction, field emission scanning electron microscopy, transmission electron microscopy, energy-dispersive X-ray spectroscopy (EDS), X-ray photoelectron spectroscopy, and high-angle annular dark-field scanning transmis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…It was found that Ni atoms on the surface of nickel foam entered into the formation of MnCo LDH nanoneedle arrays 23 . Also, our work proved that LDHs were not sulfurized under proper sulfurization conditions 24 . In the current work, therefore, we attempted to construct a hybrid electrocatalyst consisted of hollow Co 9 S 8 polyhedrons and MnCo LDH nanoneedle arrays on nickel foam for the OER.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…It was found that Ni atoms on the surface of nickel foam entered into the formation of MnCo LDH nanoneedle arrays 23 . Also, our work proved that LDHs were not sulfurized under proper sulfurization conditions 24 . In the current work, therefore, we attempted to construct a hybrid electrocatalyst consisted of hollow Co 9 S 8 polyhedrons and MnCo LDH nanoneedle arrays on nickel foam for the OER.…”
Section: Introductionmentioning
confidence: 76%
“…23 Also, our work proved that LDHs were not sulfurized under proper sulfurization conditions. 24 In the current work, therefore, we attempted to construct a hybrid electrocatalyst consisted of hollow Co 9 S 8 polyhedrons and MnCo LDH nanoneedle arrays on nickel foam for the OER. Firstly, ZIF-67 polyhedrons loaded on the preprepared NF-supported MnCo LDH nanoneedle arrays; then, the above arrays were sulfurized to form the final product.…”
Section: Introductionmentioning
confidence: 99%
“…These results indicate that the PdRuTeNR electrocatalyst allows more effective accessibility of its electrocatalytic active sites. [36][37][38][39] Additionally, we conducted CV studies on Pd, Ru and RuO 2 to look into the reduction potential of our suggested PdRuTeNRs (Fig. S4 †).…”
Section: Nanoscale Papermentioning
confidence: 99%
“…OER performance of recently reported CoFe bimetallic powder catalyst. References [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] are cited in the supplementary materials.…”
Section: Supplementary Materialsmentioning
confidence: 99%